P199 Molecular Analysis Demonstrates Shared Strains Of Mycobacterium Abscessus Isolates In Cystic Fibrosis Patients Attending A Single Centre. (10th November 2014) - Green, HD; Bright-Thomas, Rowland; Barry, PJ; Woodford, N; Isalska, B; Horsley, A; Kenna, D; Jones, AM
Abstract : Introduction and objectives: The Mycobacterium abscessus complex is an emerging group of pathogens in cystic fibrosis (CF), which may cause cross infection. The aim of this study was to determine whether CF patients infected with M.abscessus attending a single UK adult CF centre harboured unique or shared strains of M. abscessus. Methods: Isolates were from 12 patients attending a single adult CF centre, who yielded one or more positive sputum cultures for M. abscessus complex during the period January 2010 to August 2013. Isolates were identified to subspecies level using hsp65-rpoB concatenated sequence cluster analysis. Variable Number Tandem Repeat (VNTR) analysis was used to compare these isolates and determine whether two or more patients were infected with the same strain. Results: 11 isolates were identified as M. abscessus susbp. abscessus . VNTR analysis demonstrated 2 clusters of 6 and 2 patients carrying the same strains of M. abscessus susbp. abscessus, both of which have also been isolated from CF patients from other UK hospitals. Isolates from the remaining 3 patients were unique. One additional isolate was identified as M. abscessus subsp.bolletii. No clear epidemiological connexions between patients within each cluster at our centre have been identified to date. Conclusion: These results provide further evidence that some strains of M. abscessus complex may be isolated from multiple CF patients. However, there were no clear epidemiological connexions between patients within clusters at our centre. The same strains have been isolated from patients at different UK CF centres. Further studies are required to determine the mode of acquisition of infection with these strains and whether there is a common environmental source of infection or cross infection between patients.